Multi-axis stress sensing of bending and torsion using nano-diamond NVC fixed on a Si cantilever - Kanta Yamakawa; Yuta Ochiai; Takahito Ono; Masaya Toda (Functional Diamond)
In this study, we developed a cantilever-type force probe with a nano-diamond nitrogen vacancy color center (NVC) fixed on Si surface by sputtered SiO2 layer. We explored the correlation between the optically detected magnetic resonance (ODMR) spectrum’s peak shift and the stress intensity caused by the cantilever’s vibration. By adjusting the crystal axis of the nano-diamond and the static magnetic field, we assessed the peak shift’s dependency on these variables. Our results indicated that the peak shift could effectively detect uniaxial stress from standard vibration. Moreover, with increasing vibration amplitude, the peak shift proportionally intensified, consistent with theoretical expectations. For multi-axial vibration involving torsion, we noted multiple peak shifts in positive direction, suggesting stress along the axis. These findings confirm the potential of nano-diamonds on cantilevers to measure multiaxial stress.